(untitled) (Journal of Dhaka National Medical College & Hospital, 2021)
Objective: The aim of the present study was to assess the severity of pain according to visual analog scale in adhesive capsulitis patients with DM. Methods: A descriptive, cross sectional study was conducted from January 2019 to June 2019 among 200 patients attending at Physical Medicine and Rehabilitation Department, Bangabandhu Sheikh Mujib Medical University after obtaining requisite consent from the patients. Purposive sampling was adopted for collecting data. Data were collected through the assessment of patients in the Outpatient Department. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the severity of pain according to visual analog scale in adhesive capsulitis patients. The study was approved by the institutional ethical committee. Results: Mean age of patients with adhesive capsulitis was 54.85±9.35 years. Among 200 DM patients, majority (35%) was between 51-55 years. Among 200 patients 61% was female and 39% was male. Among the DM patients 54(27%) had adhesive capsulitis, and 146(73%) did not have adhesive capsulitis. Female patients (65%) suffered from more adhesive capsulitis of shoulder than male patients (35%). Most of the adhesive capsulitis patients suffering from moderate type of pain which visual analogue score is 4-6. Conclusion: Overall frequency of adhesive capsulitis of the shoulder among diabetic individuals attending in physical medicine and rehabilitation department of a tertiary care hospital was 27%. Most of the adhesive capsulitis patients suffering from moderate type of pain which visual analogue score is 4-6. J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 21-23